A Study on Figurative Language Used in the Selected Songs of The “Encanto” Movie’s Soundtrack - Suhendar, Suhendar; Brenda .K, Avrillia Kezia; Budiarto, Budiarto (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2024)
Practically, this research engages literary works to critically examine the figurative language represented in recent Disney animated films’ soundtrack, “Encanto”, which was released in 2021. Meanwhile, the urgency of this research is the need of thorough understanding of figurative language in the song’s lyrics. In relation to which, the objectives of this research is to find the kinds, the most dominant usage and general meaning of figurative language used in the selected songs of the original soundtrack of Disney’s animated film “Encanto”. As for the works of this research, it is to unpack the constructions of the figurative language through an analysis of the figuration of the Disney movie’s soundtrack. In this matter, this research analyze the lyrics which are discursively embodied in these Disney movies in complex and contradictory ways, for such and therefore Disney works on and through these bodies are then accordingly undertaken to fix and contain the ideological constructions of language, literature, and culture. Since language gives people the spirit and symbolic of expressions, in order to gather the aforesaid objectives, the researchers use qualitative method with descriptive approach, by gathering information mainly from books and international journals. The researcher discovered nine different kinds of figurative languages namely metaphor, simile, metonymy, irony, personification, paradox, hyperbole, synecdoche, and idiom. Apparently the researcher identified that the most figurative language used in such Disney’s animated film “Encanto” is metaphor.